Modifikasi Desalinator Tenaga Surya Berfilter - Margaretta, Desyana Olenka (JURNAL INTEGRASI, 2024)
The fact that Indonesia is a maritime country with a land area of 1,910,931.32 km2 and ocean 3,544,743.9 km2. 64.97% of Indonesia's total area is water, but there are still many areas that lack clean water. Problems in some areas during the summer season also occur in the southern littoral region of Tulungagung. Potential seawater should be used for efforts to overcome water scarcity in local areas. We conducted preliminary research to purify seawater so it could become fresh and drinkable. A prototype model from previous researchers was modified and added a number of natural materials as filters. This natural material utilizes local Tulungagung resources, one of which is marble industry waste. The results showed that the prototype reduced the salinity of sea water from 23 "° to 0.167 "° or reached 97%.